The Feasibility of Magazine Media with Utilization of Indonesian Biodiversity Submaterial Based on Medicinal Plants - Dewi Kurnia; Syamswisna Syamswisna; Andi Besse Tenriawaru (Journal of Biology Learning, 2022)
This study aims to determine the appropriate use of learning media in the form of media for the use of sub-materials for the use of Indonesian biodiversity for class X, plant-based high schools. The research method used is descriptive. The research was conducted in 2 stages, namely plant inventory and media feasibility test. Inventory of medicinal plants in the village of Selat Remis was carried out by means of observation, interviews, and documentation. The results of the plant inventory in Selat Remis Village found 77 species of plants used by the community as used according to needs carried out in three stages of media creation, media validation, and data analysis. The magazine media was validated by two Biology education lecturers and three high school teachers who were determined using purposive sampling, namely, State Senior High School 1 Teluk Pakedai, State High School one Rasau Jaya, and Madrasah Aliyah Negeri 1 Kubu Raya. The validation assessment uses a Likert scale and data analysis based on the Lawhse formula (1975) by five validators and obtains a Content Validity Index (CVI) result of 1.00 so that the contents of the magazine media on the sub-material of the use of Indonesian biodiversity for class X Senior high school are said to be valid and feasible to use.